Property Structure of Stock Exchanges and Market Quality: A Study of the Bovespa Demutualisation (International Journal of Banking and Finance, 2016)
This article investigates the hypothesis that the property structure of organisations is related to the quality of the products and services that they supply. The analysis is accomplished through the study of the Brazilian stock exchange (Bovespa), which modified its property structure through demutualisation and capital opening at the end of 2007. According to the New Institutional Economics (NIE), the modification of property structures could result either in the deterioration of quality, due the need of for-profit firms to increase profits and cut costs, or improvement in quality, due to increases in efficiency. This question is evaluated through Lumsdaine and Papell’s (1997) endogenous two structural break test applied on the average bid-ask spread of all stocks traded on the Bovespa. The result indicates that there is a significant break in the series trend during the demutualisation process, suggesting that the property structure change led to an improvement in market quality.